Cursos de geologia: expansão, interiorização e consolidação do ensino de geologia no brasil - Fuck, Reinhardt Adolfo; Verissimo, César Ulisses Vieira; De Oliveira Neri, Tereza Falcão; De Castro, David Lopes; Neto, José Araújo Nogueira; Sabadia, José Antonio Beltrão; Vasconcelos, Sònia Maria Silva; Parente, Clovis Vaz; De Carvalho, Maria Geralda; De Rosa Nummer, Alexis; Citroni, Sérgio Brandolise; Macambira, Joel Buenano; et al. (My University, 2008)
A short time after the creation of the first Geology courses in Brazil (in 1957 with the pioneers in the University of São Paulo and in the Federal Universities of Ouro Preto, Pernambuco and Rio Grande do Sul, and then in the following year in the Federal Universities of Bahia and Rio de Janeiro), there arose other initiatives that spread almost twenty Geology courses throughout Brazil. In addition to expanding the Geology teaching in the South, Southeast and Northeast regions, these initiatives succeeded in allowing access to geological education for the population in the North and Central-west of Brazil. In the 1960s, the courses in the Federal University of Para in Belém (1964), University of Brasilia (1965) and São Paulo State University in Rio Claro (1969) were implanted. In the following decade, the courses in the Federal Rural University of Rio de Janeiro in Seropédica (1970), the Federal University of Ceará in Fortaleza (1970), the University of Rio dos Sinos in São Leopoldo (1973), the Federal University of Paraná in Curitiba (1973), the Federal University of Minas Gerais in Belo Horizonte (1973), the Federal University of Amazonas in Manaus (1976), the Federal University of Mato Grosso in Cuiabá (1976), the Federal University of Rio Grande do Norte in Natal (1976), and the State University of Rio de Janeiro in Rio de Janeiro (1977) were all created. At the close of the twentieth century, the course was implanted in the State University of Campinas (1998). Now, at the beginning of the twenty-first century, new Geology courses are being implanted, accentuating the movement inland of Geology teaching in Brazil. The Federal University of Pará began a new course in its campus in Marabá in the south-east of Pará and the Federal University of Bahia implanted a new course in its campus in Barreiras in the west of Bahia. Finally, the Federal Universities of Sergipe, Espírito Santo and Roraima commenced Geology courses in Aracaju, Alegre and Boa Vista, respectively. This chapter will present the synthesis of the Geology courses which, over the last decades of the twentieth century, contributed to the expansion of Geology teaching in the country, taking it to every region and giving opportunities to a large number of Brazilian citizens to realize their dreams and tread the paths of their professional vocation.
Geology courses: Expansion, internalization and consolidation of Geology teaching in Brazil
Keywords: curriculum; education; geology; teaching; university sector; Brazil